2022
DOI: 10.3389/fcell.2022.887107
|View full text |Cite
|
Sign up to set email alerts
|

Won’t You be My Neighbor: How Epithelial Cells Connect Together to Build Global Tissue Polarity

Abstract: Epithelial tissues form continuous barriers to protect against external environments. Within these tissues, epithelial cells build environment-facing apical membranes, junction complexes that anchor neighbors together, and basolateral surfaces that face other cells. Critically, to form a continuous apical barrier, neighboring epithelial cells must align their apico-basolateral axes to create global polarity along the entire tissue. Here, we will review mechanisms of global tissue-level polarity establishment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…One interesting phenomenon found in this organoid model is that following differentiation ECM is gradually degraded, and organoids can move and merge into larger spheroid-like structures. The recent developmental studies done in chick lungs have reported that the continuous network of airway is generated by large-scale epithelial fusion events 36 , 37 . During this fusion process, epithelial basal cells can contact each other at the fusion site, while the apical polarity is maintained (i.e., those differentiating or differentiated cells still locate at the apical layers); meanwhile, ECM around the fusion partners is degraded; finally, the merged epithelial structures form a larger scale epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting phenomenon found in this organoid model is that following differentiation ECM is gradually degraded, and organoids can move and merge into larger spheroid-like structures. The recent developmental studies done in chick lungs have reported that the continuous network of airway is generated by large-scale epithelial fusion events 36 , 37 . During this fusion process, epithelial basal cells can contact each other at the fusion site, while the apical polarity is maintained (i.e., those differentiating or differentiated cells still locate at the apical layers); meanwhile, ECM around the fusion partners is degraded; finally, the merged epithelial structures form a larger scale epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of a single lumen is essential for the development of several epithelial structures in vivo , including the mouse epiblast 128 and zebrafish Kupffer’s vesicle, an organizer tissue that is functionally analogous to the mouse node 12 , 129 131 . In addition, the fusion of multiple lumens leads to the generation of tubular and branched epithelial structures 132 , including the zebrafish gut 119 , 133 , 134 and neural tube 66 , 67 , 135 , the Ciona notochord 68 , 136 , and the mouse pancreas 34 , 35 , kidney 37 , and heart 72 , 137 . These results demonstrate that lumen formation is a basic unit of epithelial organization that can be mobilized to generate diverse epithelial structures.…”
Section: Discussionmentioning
confidence: 99%
“…How cell signaling pathways and transcription factors regulate these cellular processes is poorly understood. Similar epithelial fusion events occur in other tissues including the heart, oral palate, eyes, and neural tube; organ systems that are frequently disrupted in complex EA/TEF patients, suggesting common biological mechanisms 14 . Studies in these other organs indicate that dynamic changes in tissue and cell polarity are necessary for proper morphogenesis 14,15 .…”
Section: Introductionmentioning
confidence: 88%
“…Similar epithelial fusion events occur in other tissues including the heart, oral palate, eyes, and neural tube; organ systems that are frequently disrupted in complex EA/TEF patients, suggesting common biological mechanisms 14 . Studies in these other organs indicate that dynamic changes in tissue and cell polarity are necessary for proper morphogenesis 14,15 . For example, vertebrate neural tube closure and morphogenesis of the Drosophila retina both require the spatial-temporal coordination of apical-basal and planar cell polarity (PCP) proteins, but how polarity and junctional proteins are localized and coordinated to regulate epithelial fusion and remodeling is unclear 1619 .…”
Section: Introductionmentioning
confidence: 88%